26th AIAA Applied Aerodynamics Conference 2008
DOI: 10.2514/6.2008-6916
|View full text |Cite
|
Sign up to set email alerts
|

Launch Vehicle Performance Enhancement Using Aerodynamic Assist

Abstract: A complete preliminary design model of a three-stage solid-fuel launch vehicle has been combined with a genetic algorithm to perform an optimization study with the goal to enhance performance using aerodynamic assist. Three studies have been completed which include improving the suborbital and orbital flights of a modern intercontinental ballistic missile and improving on the orbital flight of a generic threestage launch vehicle. The performance is enhanced by varying the geometric definition of the attached w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A non-intuitive observed is that the optimized vehicles apparently exhibit similar payload and fuel ratios for top, middle, and bottom stages respectively, despite the addition of wing structure. Perhaps a more compelling way to present the results relating to the enhancement of performance using aerodynamic assist is to consider the effective specific impulse as calculated using the rocket equation from dynamic, shown in Equation 4. The final calculations can be found in Table 5.…”
Section: Figure 3: Side By Side Comparison Of Optimized Vehicle Withomentioning
confidence: 98%
See 2 more Smart Citations
“…A non-intuitive observed is that the optimized vehicles apparently exhibit similar payload and fuel ratios for top, middle, and bottom stages respectively, despite the addition of wing structure. Perhaps a more compelling way to present the results relating to the enhancement of performance using aerodynamic assist is to consider the effective specific impulse as calculated using the rocket equation from dynamic, shown in Equation 4. The final calculations can be found in Table 5.…”
Section: Figure 3: Side By Side Comparison Of Optimized Vehicle Withomentioning
confidence: 98%
“…This computes to a reduction in weight of over 28%. Just as was the case with the suborbital vehicles, an analysis was performed to determine the effective propulsive specific impulse using the changes in velocities, the stage weight breakdown, and equations [1][2][3][4] defined earlier. Shown in Table 6 are the final results of this analysis for both payload configurations.…”
Section: A Minotaur Payload (738 Lb)mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar optimization based trade studies have been used to improve the design for launch vehicles without using aerodynamic assist 3 and it has been shown that the addition of some aerodynamic surfaces can, in some cases improve performance even without trajectory optimization included except for launch angle. 4,5 This effort expands significantly on that work by incorporating a new path optimization approach based on solving the inverse problem for following paths proposed by an optimizer with the help of dynamic spline fitting 6 and by improving the fidelity of the vehicle modeling capability.…”
mentioning
confidence: 99%